PENGUJIAN TEORI PECKING ORDER PADA LIFE-CYCLE PERUSAHAAN DI INDONESIA - , Bima Yudhistiar Primudyastono, Dr. Erni Ekawati, MBA., MSA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The results of research on the theory of capital structure often tend to prove the existence of the theory, but it doesnât provide a deeper understanding of the theory itself. This study tries to provide a deeper understanding of the theory of capital structure (pecking order theory) in a variety of conditions companies are categorized according to the concept of life-cycle. Using the listed companies in Indonesia Stock Exchange data from the year 1991-2010, the results of this study confirm the application of the pecking order theory in capital structure decision by companies in Indonesia. The results of this study also showed that the highest of average debt proportion occur at growth phase. Meanwhile, the average debt proportion at introduction phase is not so different with maturity phase.